Simulation of solar absorption refrigeration cycle with CuO nanofluid for summer cooling of a residential building. (1st September 2022) - Rahmani, Mehrnoosh; Shahabi Nejad, Ali; Fallah Barzoki, Mohammad; Kasaeian, Alibakhsh; Sameti, Mohammad
Highlights: A H2 O/LiBr absorption refrigeration cycle is integrated with trough collector. Constant magnetic field and nanoparticles increase the system's heat transfer. Performance of the system's energy for supplying a building is evaluated. The temperature of the outlet water from the solar collector increases by 7 °C. Abstract: The purpose of this study is to design a solar cooling system to provide the cryogenic load of a residential building. The heating cycle of a system comprises a solar trough collector, heat storage as a hot water tank, and a heat exchanger to transfer heat to the absorption cooling system converter. A constant magnetic field is used in the solar trough collector and fan-coil to increase heat transfer from magnetic nanoparticles in the collectors and nanorefrigerants in the absorption chiller evaporator. The system performance is modeled and simulated using TRNSYS. In general, the annual efficiency of the solar trough collector is above 40 %. If a magnetic field with 0.5 % nanofluid volume concentration is applied, it is seen that the maximum energy absorbed by the solar collector in the system increases by more than 250 kJ/h. However, the maximum room temperature is decreased by 2 ℃ compared to the case in which the improvements are not applied, and the minimum temperature is decreased from 12 ℃ to 9 ℃, indicating a 3 ℃ reduction. The maximum received energy occurs for a 770 T magnetic field with a nanofluid volume concentration of 0.5 %, where the received energy is 7000 kJ/h.